Cognitive functioning over 2 years after intracerebral hemorrhage in school‐aged children. (6th September 2017) - Murphy, Lexa K; Compas, Bruce E; Gindville, Melissa C; Reeslund, Kristen L; Jordan, Lori C
Abstract : Aim: Previous research investigating outcomes after pediatric intracerebral hemorrhage (ICH) has generally been limited to global and sensorimotor outcomes. This study examined cognitive outcomes after spontaneous ICH in school‐aged children with serial assessments over 2 years after stroke. Method: Seven children (age range 6–16y, median 13; six males, one female; 57% white, 43% black) presenting with spontaneous ICH (six arteriovenous malformations) were assessed at 3 months, 12 months, and 24 months after stroke. The Pediatric Stroke Outcome Measure (PSOM) quantified neurological outcome and Wechsler Intelligence Scales measured cognitive outcomes: verbal comprehension, perceptual reasoning, working memory, and processing speed. Results: PSOM scales showed improved neurological function over the first 12 months, with mild to no sensorimotor deficits and moderate overall deficits at 1‐ and 2‐year follow‐ups (median 2‐year sensorimotor PSOM=0.5, total PSOM=1.5). Changes in cognitive function indicated a different trajectory; verbal comprehension and perceptual reasoning improved over 24 months; low performance was sustained in processing speed and working memory. Age‐normed centile scores decreased between 1‐ and 2‐year follow‐ups for working memory, suggesting emerging deficits compared with peers. Interpretation: Early and serial cognitive testing in children with ICH is needed to assess cognitive functioning and support children in school as they age and cognitive deficits become more apparent and important for function. What this paper adds: In children with intracerebral hemorrhage (ICH), motor function improved between 3 months and 24 months. Improvements in cognitive function were variable between 3 months and 24 months. Working memory centiles declined, suggesting emerging deficits compared with peers. Processing speed improved but remained significantly below the 50th centile. Cognitive impact of ICH may increase with age in children. What this paper adds: In children with intracerebral hemorrhage (ICH), motor function improved between 3 months and 24 months. Improvements in cognitive function were variable between 3 months and 24 months. Working memory centiles declined, suggesting emerging deficits compared with peers. Processing speed improved but remained significantly below the 50th centile. Cognitive impact of ICH may increase with age in children. This article is commented on by Greenham on page1104 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.